Prevalence and risk factors of musculoskeletal injuries in modern and contemporary dancers: a systematic review and meta-analysis - Yufei Sun; Hui Liu (Frontiers in Public Health, 2024)
BackgroundA large number of studies have found that the musculoskeletal injury of modern and contemporary dancers has a high incidence. Previous publications have indicated that there are many potential factors that are related to dancing injury; however, they have not been proven, and even some data are conflicting in different research.ResultsThe search yielded 18 prospective studies reporting on professional and pre-professional modern or contemporary dancers from companies and schools. The prevalence of modern and contemporary dancers was 0.82 (95% CI: 0.74~0.90). The injury proportion of trauma, overuse, ankle and foot, lower extremity, joint and ligaments, muscle and tendons, and time-loss were 0.40, 0.26, 0.49, 0.34, 0.33, and 0.29 in the total number of injuries. There was no evidence of a significant difference in sex, age, and education program. The factors of BMI and injury history achieved statistical significance, and the p-values were less than 0.01.ConclusionBased on the results of this article, BMI and injury history may be risk factors for injury in contemporary and modern dancers. Modern and contemporary dancers have a high prevalence of musculoskeletal injuries. Lower extremity injuries are the most common in the whole body, with injuries to the foot and ankle being more frequent. The mechanism of injury is mostly overuse injury, and the injured tissues are mostly muscle tendons and joint ligaments.